Assessing soil attributes in puddled no-tilled vs. tilled fields amid an irrigation cycle using electrical resistivity - Swileam, Gamal S. M.; Shahin, Reda R.; Abdelkader, Noha H.; Essa, Khalid S. A. (Journal of Aridland Agriculture, 2026)
The objective of this study was to determine the effectiveness of electrical resistivity (ER) for monitoring soil management systems – conventional tillage (CT) and puddled no-till (PNT) throughout an irrigation cycle in a field located in El-Fayoum, Egypt. We selected a pair of adjacent fields, one dominated by CT and another with PNT. The two fields were basin irrigated and measurements of soil moisture (%, SM), salinity (EC, dS m-1), bulk density (BD, g cm-3), and ER were taken at 3, 15, and 30 days post-irrigation. Conventional tillage (CT) enabled salt to be redistributed within the soil profile, decreasing surface salt content that originated from soil disturbance. In contrast, PNT experienced its soil surface salinity level increase rapidly as salts were trapped in the compacted topsoil. By day 30, salinity in the PNT plot was 3.0-5.6 dS m-1 higher than in the CT plot, demonstrating a limitation of PNT related to excessive salt accumulation, especially under arid conditions. While the CT plot had lower BD initially and became more compacted over time, compaction increased in the PNT treatment throughout the study mostly due to its high compaction level resulting from puddling. Application of 2D Apparent Electrical Resistivity Tomography (AERT) and 1D layered resistivity models (LERM) to ER measurements revealed significant ER pattern differences between the two systems. Puddled no-till (PNT), especially in the topsoil, showed lower ER rates due to the pronounced high moisture and salinity. Conventional tillage (CT) demonstrated greater ER variation, which improved with the migration of water. The statistical analysis validated the strong positive correlation of higher moisture, salinity, and BD with lower ER values. Overall, this study showed that ER methodology could be effective in assessing soil behavior under various tillage systems quickly and non-destructively.